Pengaruh Pembelajaran Berbasis Game Menggunakan Kahoot Terhadap Penguasaan Kosakata Bahasa Inggris Mahasiswa Baru - Penton, Serly Susanti (Peneliti.net, 2025)
This research investigates the impact of game-based learning through the kahoot platform on the English vocabulary proficiency of first-year students enrolled in the English study program at Tribuana university of Kalabahi. Utilizing a quasi-experimental design featuring a single group with pre-tests and post-tests, the study include 22 students from the 2024/2025 academic year. Data collection methods comprised vocabulary tests, questionnaires, classroom observations, and semi-structures interviews. The findings indicated a statistically significant enhancement in students’ vocabulary scores following the kahoot-based intervention (p < 0.001), with the average score increasing by 4 points. Insights from the the questionnaires and interviews highlighted elevated levels of student motivation, enjoyment, and engagement. Students expressed that kahoot’s interactive elements, including real-time feedback and gamified quizzes, enriched their learning experience and facilitated more effective vocabulary acquisition. Observations also revealed heightened participation and collaboration during the learning sessions. Despite encountering minor issues such as internet connectivity, these challenges did not substantially impede the learning process. It can be said that kahoot serves as an effective digital learning resource for improving vocabulary mastery while promoting a more dynamic, inclusive, and student-centered learning atmosphere. These results imply that incorporating gamified learning platforms can be a beneficial approach in English language instruction, especially with higher education settings taht cater to diverse learner needs.